UJI AKTIVITAS PENYUBUR RAMBUT KOMBINASI EKSTRAK AIR TEH HIJAU DAN HERBA PEGAGAN - Lela Sulastri; Teti Indrawati; Shelly Taurhesia (Universitas Ahmad Dahlan, 2016)
Hair fertilizer was used to stimulate hair growth that is used topically on the scalp. Natural materials are expected to be used as fertilizer hair is green tea leaves and herb gotukola. Because the green tea leaves contain a chemical polyphenol compounds that are flavonoids and their derivatives and herb gotukola contain lead compound triterfenoid saponin that are asiatikoside, flavonoids, phytosterols, madecassid acid, madecassoside, asiatic acid and amino acids are thought to have properties as fertilizer hair. This study was conduced to determine whether the combination of the water extract of green tea leaves and herb gotukola has activity as a hair fertilizer and combination which has the most optimum activity. Test hair fertilizer activities include the rate of hair growth, hair growth acceleration and the weight of the hair. In this study used three combinations are combination 1 ( the water extract of green tea leaves and 5% water gotukola herb extract 2.5%), combination 2 (the water extract of green tea leaf extract 7.5% and 2.5% water gotukola herb) and combination 3 (the water extract of green tea leaves and 5% water gotukola herb extract 7.5%). The results showed the combination of the water extract of green tea leaves and water extract herb gotukola has activity as fertilizer hair and extract the most optimum combination is a combination of 1 with a concentration of water extract of green tea leaves (5%) and water extract of the herb gotukola (2.5%) the rate of hair growth 2.689 cm in 28 days, accelerated hair growth 0.128 cm / day and the hair weighs 0.1938 grams in 28 days.